2020
DOI: 10.3390/ma13184049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Bioactive Glass Composition on Biological Properties of Human Dental Pulp Stem Cells

Abstract: Functional reconstruction of bone defects represents a clinical challenge in the regenerative medicine field, which targets tissue repair following traumatic injuries and disease-related bone deficiencies. In this regard, the optimal biomaterial should be safe, biocompatible and tailored in order to promote the activation of host progenitor cells towards bone repair. Bioactive glasses might be suitable biomaterials due to their composition being able to induce the host healing response and, eventually, anti-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Furthermore, Sr, Mg, and Zn ions are known to promote a specific cellular response, activating molecular signaling involved in the cell cycle [ 64 , 66 ]. Indeed, both BGMS10 and BGMS_2Zn resulted very promising compositions, suitable for the preparation of granules, scaffolds and composite systems, giving also very encouraging results in vitro in innovative 3D models with human mesenchymal stem cells [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sr, Mg, and Zn ions are known to promote a specific cellular response, activating molecular signaling involved in the cell cycle [ 64 , 66 ]. Indeed, both BGMS10 and BGMS_2Zn resulted very promising compositions, suitable for the preparation of granules, scaffolds and composite systems, giving also very encouraging results in vitro in innovative 3D models with human mesenchymal stem cells [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, CHIT_PEO composite electrospun mats with Sr and Mg containing bioactive glasses and Zn-containing bioactive glasses have not been fabricated yet. To this purpose, we decided to incorporate in CHIT_PEO fibers two novel bioactive glasses: BGMS10 [ 36 , 37 , 38 , 39 ] and BGMS_2Zn [ 37 , 40 ], which resulted to be very promising in various applications in terms of biological properties, also in contact with human dental pulp stems cells and human mesenchymal stem cells [ 39 , 41 ]. Furthermore, preclinical studies in animal models using BGMS10 and BGMS_2Zn particulates are on-going.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium disks were mounted with DABCO (Sigma-Aldrich, St. Louis, MO, USA) anti-fading medium on cover glasses. Cell proliferation and morphology were investigated using confocal microscopy (Nikon A1, Nikon, Tokyo, Japan), as formerly described by Di Tinco et al [ 56 ]. Cell proliferation was measured by counting the DAPI-positive nuclei on 5 randomly selected fields measuring 4.4 × 10 4 µm 2 on 3 disks for each experimental group by a blind operator.…”
Section: Methodsmentioning
confidence: 99%
“…[88] Subsequently, Rosanna et al studied the effects of BGMS10 on the cell adhesion, morphology, proliferation, immunomodulation, and osteogenic differentiation of human dental pulp stem cells (hDPSCs) (Figure 8e,f). [87] The results showed that BGMS10 can maintain the biological properties of hDPSCs and promote the deposition of bone matrix-related proteins. Meanwhile, BGMS10 did not change the immunomodulation ability of hDPSCs and maintained the expression of FasL, a key molecule that mediates the immunomodulation effects of hDPSCs, which is a significant factor for the success of implantation and the realization of osseointegration.…”
Section: Bgs Promote Bone Formationmentioning
confidence: 95%
“…Meanwhile, BGMS10 did not change the immunomodulation ability of hDPSCs and maintained the expression of FasL, a key molecule that mediates the immunomodulation effects of hDPSCs, which is a significant factor for the success of implantation and the realization of osseointegration. [87]…”
Section: Bgs Promote Bone Formationmentioning
confidence: 99%